Remarks on Exponential Stability of Solutions for the Compressible p-th Power Newtonian Fluid with Large Initial Data (Journal of Partial Differential Equations, 2020)
In this paper, we establish the exponential stability of the global spherically and cylindrically symmetric solutions in H^i (i=1,2,4) for the p-th power Newtonian fluid in multi-dimension with large initial data. The key point is that the smallness of initial data is not needed if the initial data are cylindrically symmetric.
Keywords: Newtonian fluid; global existence; asymptotic behavior; exponential stability